Distal ulnar changes in children with thalassemia and deferiprone related arthropathy. Issue 12 (13th August 2013) - Sharma, Rajni; Anand, Rama; Chandra, Jagdish; Seth, Anju; Pemde, Harish; Singh, Varinder
Abstract Background Regular blood transfusion and iron chelation are the standard of care for children with thalassemia. Deferiprone is an effective oral iron chelator but is known to cause significant arthropathy. Though clinical and radiographic features of deferiprone related arthropathy have been described, the long‐term effects are not known. Procedure Routine radiographs of left wrist and hand done for bone age estimation in 40 children with thalassemia were evaluated and revealed unique radiographic changes in 13 children (10 males: 3 females) with previous or current deferiprone related arthropathy. Subsequently, these children underwent radiographs of both the knee joints. Results The changes on wrist X‐ray included lucency and thinning of the ulnar metaphysis, small ulnar epiphysis, deformation and impaired growth of the physeal cartilage leading to reduced distance between the epiphysis and metaphysis. The knee radiograph showed subchondral flattening of femoral and tibial condyles with irregular articular margins. Conclusions Bony dysplasia, deformation and impaired growth of ulnar epiphyses, metaphyses and physes may be an expression of deferiprone related arthropathy in children with thalassemia major. Pediatr Blood Cancer 2013;60:1957–1962. © 2013 Wiley Periodicals, Inc.